2021
DOI: 10.1109/access.2021.3073086
|View full text |Cite
|
Sign up to set email alerts
|

An Early Detection of Asthma Using BOMLA Detector

Abstract: Asthma is a chronic and airway-induced disease, causing the incidence of bronchus inflammation, breathlessness, wheezing, is drastically becoming life-threatening. Even in the worst cases, it may destroy the quality to lead. Therefore, early detection of asthma is urgently needed, and machine learning can help identify asthma accurately. In this paper, a novel machine learning framework, namely BOMLA (Bayesian Optimisation-based Machine Learning framework for Asthma) detector has been proposed to detect asthma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 53 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Step 1: Using Oversampling method for converting imbalanced dataset to balanced dataset [15]. Dataset balancing was done by oversampling technique SMOTE [16] and ADASYN [17]- [20]. SMOTE The original imbalanced dataset had total 70943 records.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Step 1: Using Oversampling method for converting imbalanced dataset to balanced dataset [15]. Dataset balancing was done by oversampling technique SMOTE [16] and ADASYN [17]- [20]. SMOTE The original imbalanced dataset had total 70943 records.…”
Section: Methodsmentioning
confidence: 99%
“…The number of records for disease diagnosed is less than the number of records where disease is not diagnosed. Therefore, an Ensemble approach was used for Hypoglycemia detection analysis using superficial body parameter readings [16], [17].…”
Section: Ensemble Approach Usedmentioning
confidence: 99%
“…After the preprocessing, mainly three classification algorithms were applied: XGB, RF, and SVM. These classifiers provide improved results in many studies [ 21 , 22 , 23 ]. Furthermore, studies found significantly improved results by applying XGB in COVID-19 mortality prediction and prepared a clinically operable Covid decision support system using XGB for clinical staff [ 23 , 24 ].…”
Section: Analysis Proceduresmentioning
confidence: 99%
“…Awal et al [ 114 ] applied multiple learning models to investigate the parameters that characterize asthma diagnosis and prediction. BOMLA (Bayesian Optimisation-based Machine Learning Framework for Asthma), a new machine learning technique, had been developed for identifying asthma.…”
Section: Introductionmentioning
confidence: 99%